The Early Dakhmas of Bactria - Shapulat В. Shaydullaev; Ladislav Stančo; Kahramon B. Toshaliev (Археология евразийских степей, 2025)
The article deals with the first dakhmas (Towers of Silence) discovered in the Kohitang Mountain and its foothills, located in the Sherobod district of the Surxondaryo region of the Republic of Uzbekistan, during international expeditions—the Uzbek-Czech and the Uzbek-French expeditions. The text provides general information about dakhmas, their location in Central Asia, as well as a brief historiography. Previous research has established that Zoroastrianism spread in Central Asia at the end of the Bronze Age or the beginning of the Iron Age. However, these studies do not mention the spread of the first dakhmas, which are the primary structures of Zoroastrianism. Field studies conducted by international expeditions have helped fill this gap. The specifics of the burial rites allow the discovered structures to be identified as the earliest dakhmas of Bactria and shed light on the question of where ancient Zoroastrianism originated.